Intravaginal Pulsed Contractile Radiofrequency for Stress Urinary Incontinence Treatment; A Safety Study: Pulsed Contractile Radiofrequency in the Treatment of Stress Urinary Incontinence - Razzaghi, Mohammadreza; Asghari-azghan, Afsar; Montazeri, Saeed; Razzaghi, Zahra; Mazloomfard, Mohammad Mohsen (Journal of Lasers in Medical Sciences, 2021)
Introduction: Radiofrequency (RF)-based stress urinary incontinence (SUI) treatment, which has quickly attracted attention, is administered in an office setting. This pilot-safety study assessed the efficacy of transvaginal RF treatment in the quality of life (QOL) and frequency of incontinence episodes in women with SUI. Methods: Twenty-eight women suffering from SUI were treated with an intravaginal quadric applicator while a grounding pad was attached in front of their pubes. The first phase is thermic, which will heat up the vaginal wall up to 40°C for 10 minutes. The second step is contraction to stimulate an aerobic exercise of pelvic floor muscles for 20 minutes (pulsed contractile RF at 20-40 watts and 1000-300 kHz with modulation of 1 to 300 Hz for muscle exercise). It was scheduled for one session per week for 3 sessions. Patients had follow-up visits before and 1, 6, and 12 months following the treatment for a one-day voiding diary, the Persian version of urinary incontinence QOL questionnaire (I-QOL), Q-tip test, 24 hours-pad test, and daily incontinence episodes’ number. Results: The patients’ mean age, duration of incontinence, and median vesical leak point pressure were 41.6±9.6 years, 5.48±6.84 years, and 140 cm H2 O respectively. Significant changes were observed in the mean I-QOL total score and the pad test. Also, a notable reduction was observed in the number of daily leakage episodes and the Q-tip test at any follow-up visit (P=0.001). Conclusion: Preliminary results suggest that transvaginal RF is a convenient method of SUI treatment. Significant changes were observed in the mean I-QOL total score and the pad test. Also, a notable reduction was observed in the number of daily leakage episodes. DOI: 10.34172/jlms.2021.56